2005
DOI: 10.1677/erc.1.00871
|View full text |Cite
|
Sign up to set email alerts
|

Effect of small-sized liposomal Adriamycin administered by various routes on a metastatic breast cancer model

Abstract: The antitumor effects of small-sized liposomal Adriamycin (LADR) administered by various routes were investigated in rabbits bearing well-developed VX2 tumors in the mammary gland. Rabbits received s.c. or i.v., or s.c. combined with i.v., injections of LADR 6 weeks after tumor implantation. The i.v. route showed a significant inhibitory effect on breast tumors and distant metastases. In comparison, metastases in axillary and mediastinal lymph nodes were more efficiently inhibited after s.c. injection. LADR ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…In addition a similar study by Chen et al [24] indicated that Adriamycin in liposomal form targeted diffuse breast cancer cells, however, not only massive amounts of Liposomes were absorbed by tumor cells, but also the rate of cellular toxicity was significantly increased. Interestingly, any type of allergic reaction or toxicity was not observed by the investigators in patients.…”
Section: Discussionmentioning
confidence: 89%
“…In addition a similar study by Chen et al [24] indicated that Adriamycin in liposomal form targeted diffuse breast cancer cells, however, not only massive amounts of Liposomes were absorbed by tumor cells, but also the rate of cellular toxicity was significantly increased. Interestingly, any type of allergic reaction or toxicity was not observed by the investigators in patients.…”
Section: Discussionmentioning
confidence: 89%
“…But, the most common side-effects associated with anthracycline analogues like Dox include acute and chronic toxicities such as myelosuppression, cardiomyopathies and congestive cardiac failure [3], [4]. To overcome these side-effects, integrated approaches utilizing combination therapies with cytotoxic, chemosensitizing and nanoparticle agents have been devised.…”
Section: Introductionmentioning
confidence: 99%
“…The systemic toxicity and reduced incursion of chemotherapeutic drugs into breast tissue is leading into constant demands for developing new therapeutic agents capable of eliminating these problems and are clinically applicable against breast cancer [28]. Plants are known to possess pharmacological diversified properties and are rich source of clinically important phytochemicals against various diseases, including cancer.…”
Section: Discussionmentioning
confidence: 99%